Hubungan Career Adaptability dengan Hardiness Mahasiswa Tingkat Akhir Kependidikan Universitas Negeri Padang - Anjelika, Tiara; Kurniawan, Rizal (Lembaga Yasin AlSys, 2024)
This research aims to determine the relationship between career adaptability and hardiness of final year education students at Padang State University. This study uses quantitative methods with a correlational quantitative method design. Data collection techniques using proportionated stratified random sampling. The sample in this study amounted to 375 respondents. This research instrument uses The Career Adapt-Abilities Scale Indonesian Form scale from Sulistiani et al., (2019) and a hardiness scale based on the theory of Kobasa., et al (1982). The results of the analysis used product moment correlation and found that there was a significant relationship between career adaptability and hardiness of final year education students at Padang State University.